The first record of Neostempellina simantoneoa (Sasa, Suzuki et Sakai, 1998), comb. nov. for the Russian Far East, with a description of the preimaginal stages (Diptera, Chironomidae) - Orel, Oksana V. (Zootaxa, 2023)
Zavrelia simantoneoa (Sasa, Suzuki et Sakai, 1998) is moved to the genus Neostempellina Reiss as new combination. The pharate male of Neostempellina simantoneoa (Sasa, Suzuki et Sakai, 1998) is redescribed. The pupae and larvae collected in rivers of the southern part of Primorye Territory (Russian Far East) are described and illustrated for the first time.